2013
DOI: 10.3109/13625187.2012.728643
|View full text |Cite
|
Sign up to set email alerts
|

The influence of combined oral contraceptives on female sexual desire: A systematic review

Abstract: The majority of COC users report no significant change in libido although in most studies a decline in plasma levels of free testosterone and an increase in those of sex hormone binding globulin were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 57 publications
5
61
1
5
Order By: Relevance
“…Positive significant effects were found on menstrual cycle related symptoms as measured by the MDQ, except for the domain Arousal, showing negative effects. According to the literature, the effect of COC use on these parameters is inconsistent [3,21,[23][24][25][26]39]. In some studies the EE/DRSP COC used has been shown to improve the MDQ domains Water retention and Negative affect [40][41][42], but this was not observed in our study.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Positive significant effects were found on menstrual cycle related symptoms as measured by the MDQ, except for the domain Arousal, showing negative effects. According to the literature, the effect of COC use on these parameters is inconsistent [3,21,[23][24][25][26]39]. In some studies the EE/DRSP COC used has been shown to improve the MDQ domains Water retention and Negative affect [40][41][42], but this was not observed in our study.…”
Section: Discussioncontrasting
confidence: 63%
“…The effect of COC use on mood and sexual function has been questioned [3,21,[23][24][25][26]39], although in a recent paper by a group of COC experts the concept of "Oral Contraceptive-Associated Sexual Dysfunction" has been presented [4]. The COC only data from our study support the view that COC use may have a negative effect on sexual function.…”
Section: Accepted M Manuscriptsupporting
confidence: 47%
See 1 more Smart Citation
“…First, there is mixed evidence across studies: some report negative associations between desire and OC use, others find no effect, and still others report positive effects (for recent reviews, see Burrows, Basha, & Goldstein, 2012;Davis & Castano, 2004;Pastor, Holla, & Chmel, 2013;Schaffir, 2006). Second, within their respective samples, studies also consistently report considerable individual variation in women's experience: relatively large proportions of women experience a marked increase or decrease in desire, with others unaffected (Burrows et al, 2012;Davis & Castano, 2004;Pastor et al, 2013;Schaffir, 2006). For example, in a prospective study, 17% had a higher frequency of sexual thoughts and 39% had a lower frequency, following initiation of OC use (Sanders et al, 2001).…”
mentioning
confidence: 99%
“…For example, in a prospective study, 17% had a higher frequency of sexual thoughts and 39% had a lower frequency, following initiation of OC use (Sanders et al, 2001). The picture is further obscured by wide variation between studies in both methodologies and OC formulations under test, but researchers typically conclude, on the basis of these mixed effects, that the influence of OC use on sexual desire is complex and likely due to multiple psychosocial influences (Burrows et al, 2012;Davis & Castano, 2004;Pastor et al, 2013;Schaffir, 2006). Indeed, the most recent review concluded that "we cannot define a single indicator reliably and clearly characterizing a cause-effect relationship.…”
mentioning
confidence: 99%